The Reliability of Quarterly National Accounts in Seven Major Countries A User's Perspective - York, Robert (OECD Economics Department Working Papers, 1997)
National accounts data provide the most comprehensive overview available of developments in national economies. They are of great interest to a wide range of users of economic information. These users, which include governments formulating budgetary policies, central banks making monetary policy decisions, businesses considering investment decisions and financial institutions making judgements concerning portfolio allocation, have needs which may differ in various respects. However, since their interest generally stems from the likelihood that they will make better decisions if they are well informed about economic developments, they all have a strong interest in the accuracy of national accounts statistics. This paper examines the reliability of preliminary quarterly national accounts statistics. In particular, it considers the longer-term behaviour of the provisional estimates to GDP growth and its main expenditure components through an examination of the revisions to those ...